THE PROGNOSTIC MODEL OF ANTITUMOR EFFECT OF TARGETED DRUGS IN IMMUNOTHERAPY - V. V. Burlyaev; А. А. Davydenko; O. M. Nikolaeva; L. I. Russu; I. A. Suetina; M. V. Mezentseva (Тонкие химические технологии, 2016)
A prognostic model for constructing hypotheses about the relationship of combinations of cytokines with the proliferative activity of cancer cells is proposed. The model is based on the use of inductive inference methods. The methodology takes into account the synergistic interaction of cytokines and uses sequential construction of logical formulas for selecting groups of cytokines, a statistical analysis of contingency tables and logical integration of the obtained estimates. Implementation of the proposed method in the information system of forecasting the effect of targeted anticancer drugs in immunotherapy will greatly accelerate research in this area.